Heavy halogen atom effect on 13C NMR chemical shifts in monohalo derivatives of cyclohexane and pyran. Experimental and theoretical study - Neto, Alvaro Cunha (2009)
As a first step, a qualitative analysis of the spin-orbit operator was performed to predict the kind of organic compounds, where it could be expected that the SO/FC (spin-orbit/Fermi contact) and SO/SD (spin-orbit/spin dipolar) yield unusually small contributions to the "heavy atom effect" on 13C SCSs (substituent chemical shifts). This analysis led to the conclusion that compounds presenting strong hyperconjugative interactions involving the σ*C-X orbital (X = halogen) are good examples where such effects can be expected to take place. On the basis of such results, the following set of model compounds was chosen: 2-eq-halocyclohexane (2-eq), 2-ax-halocyclohexane (2-ax), and 2-ax-halopyran (3), to measure 13C SCSs. Such experimental values, as well as those of methane and halomethanes taken from the literature, were compared to calculated values at a nonrelativistic approach using B3LYP, and at a relativistic approach with BP86 using scalar ZORA, spin-orbit ZORA, scalar PAULI, and spin-orbit PAULI. Results from relativistic calculations are in agreement with the trends predicted by the qualitative model discussed in this work. © 2009 American Chemical Society.